Selling your network: how political skill builds social capital and enhances salesperson performance. Issue 3 (3rd July 2021) - Munyon, Timothy P.; Frieder, Rachel E.; Satornino, Cinthia B.; Carnes, Andrew M.; Bolander, Willy; Ferris, Gerald R.
Abstract: Research suggests that political skill affects how salespeople build and leverage social capital. However, there are important questions left unanswered in this relationship. First, although it is linked to specific structural characteristics of networks, it is unclear how political skill affects the overall quality of one's social network. Similarly, it is unclear if objective and subjective social network quality measurement approaches produce comparable results. Third, although theory positions political skill and social network quality as desirable personal and structural resources, it is unknown how these resources affect dyadic relationships between salespeople and clients. Finally, there is a need to assess how the dimensions of political skill differentially affect social network quality. To address these questions, we propose a new model of social network quality, examining how political skill influences social network quality and salesperson performance in a two-study investigation. We begin by predictively testing the unique contributions of objective and subjective social network quality in the relationship between political skill and sales magnitude one year later. We then extend these findings using dyadic salesperson and customer data to explore how political skill and social network quality predictively impact sales magnitude, sales frequency, and relationship performance.